2011
DOI: 10.1242/jeb.056366
|View full text |Cite
|
Sign up to set email alerts
|

Static inflation and deflation pressure–volume curves from excised lungs of marine mammals

Abstract: SUMMARY. Measured MAV was on average 7% of TLC, with a range from 0 to 16%. The pressure-volume curves were similar among species on inflation but diverged during deflation in phocids in comparison with odontocetes. These differences provide a structural basis for observed species differences in the depth at which lungs collapse and gas exchange ceases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(79 citation statements)
references
References 21 publications
6
73
0
Order By: Relevance
“…4), but was significantly higher during chuffs (11.9±3.7 l, AIC null =1099.2, AIC breath-type =913.3) compared with spontaneous breaths (5.7±1.7 l, P<0.01). The largest tidal volume recorded during this study was 18.4 l for Kolohe (94 ml kg −1 ), which was greater than that animal's estimated total lung capacity (TLC est ) of 17.3 l, based on models from excised lungs (TLCest=0.135M b 0.92 see references Fahlman et al, 2011;Kooyman, 1973).…”
Section: −1mentioning
confidence: 56%
See 1 more Smart Citation
“…4), but was significantly higher during chuffs (11.9±3.7 l, AIC null =1099.2, AIC breath-type =913.3) compared with spontaneous breaths (5.7±1.7 l, P<0.01). The largest tidal volume recorded during this study was 18.4 l for Kolohe (94 ml kg −1 ), which was greater than that animal's estimated total lung capacity (TLC est ) of 17.3 l, based on models from excised lungs (TLCest=0.135M b 0.92 see references Fahlman et al, 2011;Kooyman, 1973).…”
Section: −1mentioning
confidence: 56%
“…Theoretical modeling work indicates that the structural properties (e.g. compliance) of the various parts of the respiratory system dictate how pressure affects the distribution of gas between conducting airways and alveolar space (Bostrom et al, 2008;Fahlman et al, 2009Fahlman et al, , 2011Fitz-Clarke, 2007). High pulmonary compliance may be an important component of minimizing transpulmonary pressure gradients Leith, 1976Leith, , 1989Ridgway et al, 1969), and has also been suggested to reduce the risk of elevated blood and tissue N 2 levels, thereby minimizing the risk for DCS (Ridgway and Howard, 1979;Scholander, 1940).…”
Section: Introductionmentioning
confidence: 99%
“…The structural properties of the lungs were measured and have been discussed in a separate publication (Fahlman et al, 2011). The trachea was separated from the lungs and excess associated tissue was removed.…”
Section: Protocolmentioning
confidence: 99%
“…The relationship between pressure and volume gives an estimate of the compliance of the respiratory tract and has been successfully performed on excised lungs from terrestrial mammals (Bachofen et al, 1970), with few data documenting compliance of marine mammal lungs (Denison et al, 1971;Piscitelli et al, 2010;Fahlman et al, 2011). The compliance of the trachea has been suggested to affect the amount of air displaced from the lungs (Bostrom et al, 2008), and thereby the depth where the alveoli collapse and gas exchange ceases.…”
Section: Introductionmentioning
confidence: 99%
“…These data will be used to calculate airway resistance, pulmonary and thoracic compliance (pressure-volume relationship). The static compliance values will be compared to the data previously determined in postmortem marine mammals [11].…”
Section: Approachmentioning
confidence: 99%